1989
DOI: 10.5144/0256-4947.1989.371
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profile of Saudi Primary Schoolgirls in an Urban Region

Abstract: Two hundred eighty-five primary schoolgirls from the urban area of Thugba, Al-Khobar, in the Eastern Province of Saudi Arabia were examined anthropometrically. Hemoglobin estimations and laboratory stool analysis for ova and cysts were also performed. When compared to the standards of the US National Center for Health Statistics, the height-for-age measurements were below the median, lying between the 10th and 25th percentiles except in the 6-year-olds, who showed no stunting. This feature excludes the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This suggests that children had a good growth phase during the preschool age period and excludes the probability of severe or prolonged malnutrition in the critical growth periods of intrauterine life, infancy and the preschool ages. Similar results were reported by Rasheed et al 6 in their study on Saudi children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that children had a good growth phase during the preschool age period and excludes the probability of severe or prolonged malnutrition in the critical growth periods of intrauterine life, infancy and the preschool ages. Similar results were reported by Rasheed et al 6 in their study on Saudi children.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies from other Arab Gulf states such as those from Oman and Saudi Arabia 4 – 6 20 also showed that children in these countries were shorter and lighter than their counterparts in the present study. However, a recent study by El Mouzan et al for the development of reference growth charts of Saudi children and adolescents showed comparable findings for height and weight.…”
Section: Discussionsupporting
confidence: 73%
“…In Saudi Arabia most of the studies on anemia werebased on nutritional status and concentrated on preschool children who were under six years old [El Hazmi et al, 1998;Rasheed et al, 1989;Sabai et al, 1981;Sadeghipour et al, 1996].In Saudi Arabia, anemia is often aggravated by repeated and closely spaced pregnancies. Al-Ahsa is a small city located in the eastern province of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, anemic children tend to do poorly on vocabulary, reading, and other tests [11] . In Saudi Arabia most of the studies on anemia were based on nutritional status and concentrated on preschool children who were under six years old [12][13][14][15][16] , so data on the nutritional status of children and adolescents in the Kingdom are insufficient [17,18] .…”
Section: Introductionmentioning
confidence: 99%